1981
DOI: 10.1002/bip.1981.360200923
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco mosaic virus as a carrier for small molecules: Artificial receptor antibodies and superhormones

Abstract: SynopsisPeptide agonists covalently attached to tobacco mosaic virus exhibit such unusual properties as superpotency, superaffinity, enhanced resistance towards enzymic degradation, and prolonged action at the target cell. These properties can be exploited for the isolation by density-gradient centrifugation of membrane vesicles bearing specific receptors for the peptides and for radioactive and fluorescent labeling of cell-surface receptors. Our observations can be explained by cooperative-affinity phenomena … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
12
0

Year Published

1984
1984
1996
1996

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 10 publications
4
12
0
Order By: Relevance
“…Pretreatment The present results are in complete agreement with our earlier results on fluorescence labeling of these cells using a water-soluble class of fluorescent melanotropic macromolecular reagents (6, 7) as well as with those of Schwyzer and coworkers, who developed conjugates of MSH with tobacco mosaic virus (8)(9)(10)(11)(12). Using the melanotropin fluorescein conjugate, we demonstrated that both melanotic as well as amelanotic human melanoma cells expressed membrane melanocortin receptors (6,7).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Pretreatment The present results are in complete agreement with our earlier results on fluorescence labeling of these cells using a water-soluble class of fluorescent melanotropic macromolecular reagents (6, 7) as well as with those of Schwyzer and coworkers, who developed conjugates of MSH with tobacco mosaic virus (8)(9)(10)(11)(12). Using the melanotropin fluorescein conjugate, we demonstrated that both melanotic as well as amelanotic human melanoma cells expressed membrane melanocortin receptors (6,7).…”
Section: Discussionsupporting
confidence: 92%
“…In this respect, these results are similar to electron microscopic visualization of internalized receptor-ligand complex for a glucagon-serum albumin preparation labeled with 17 nanometer gold particles (23). These results are consistent with those obtained earlier using fluorescent tobacco mosaic virus-MSH conjugates (8)(9)(10)(11)(12) and fluorescent polyvinyl alcohol-MSH conjugates (6, 7).…”
Section: Synthesis Of Peptide-conjugated Beadssupporting
confidence: 91%
See 3 more Smart Citations